Togo - Coffee and Cocoa Liberalization - World Bank (Washington, DC, 2012)
The reform, a key component of a larger economic recovery and adjustment operation, and of the agricultural sector strategy, focused on the liberalization of coffee and cocoa prices, their primary marketing and export, all previously regulated by a marketing board. The main objectives of the liberalization were to improve producers' incentives and income and develop private participation in marketing and export activities while maintaining the country's reputation in international markets as a reliable supplier of quality products. The liberalization took effect in June 1996. Coffee and cocoa exports reached a record high in 1997 - more than double the 1996 level.